Code Switching in Formal setting among ESL/PKPG undergraduates of Universiti Malaysia Sarawak - Cecilia, Dharmaraj (Universiti Malaysia Sarawak (UNIMAS), 2007)
This study aims to find instances of code switching in group discussions during lecture hours among 3rd Year ESL PKPG Undergraduates of BEd. TESL programme enrolled in KMT 4053: English for Specific Purposes course. It will identify the functions reflected in each of the instances. Lastly, this paper aims to identify the factors promoting code switching. This is a case study as it is based on a single classroom. The study incorporated 3 data collection techniques: questionnaire, tape recording and interviews. The transcription of the discussion served as a basis for the interview with those who code switched. 35 participants were involved in this study where 21 participants were found to code switch during discussion. 221 instances of code switching were found and they reflected socializing function, linguistic insecurity, repetitive function, affective function, topic switch, compensation for deficiencies, meaning making, conflict control, supporting thinking and communication. Conflict control function was found to have no significance among the participants. 7 new functions of code switching were found in this study namely; attraction, agreement, conviction, serves monologues, speed up, simplify and avoid scepticism function. The factors that were identified in this study are formal versus informal regard of the participants towards discussions during lecture hours, peer influence versus no influence and absence versus presence of the lecturer. The study was basically done focusing on one particular group of undergraduates therefore it may not represent the whole population of UNIMAS undergraduates. This study incorporated in depth analysis, consequently increased the validity of the data. Therefore the findings ofthe study are a reliable one.